SERS activity with tenfold detection limit optimization on a type of nanoporous AAO-based complex multilayer substrate. Issue 11 (25th February 2016) - Sui, Chaofan; Wang, Kaige; Wang, Shuang; Ren, Junying; Bai, Xiaohong; Bai, Jintao
Abstract : The flower-patterned nanostructure developed on AAO is capable of achieving greater enhancement and lower detectable limit than its template for SERS. Abstract : Most of SERS applications are constricted by heterogeneous hotspots and aggregates of nanostructure, which result in low sensitivity and poor reproducibility of characteristic signals. This work intends to introduce SERS properties of a type of SERS-active substrate, Au-CuCl2 -AAO, which is innovatively developed on a porous anodic alumina oxide (AAO) template. Spectral measuring results of Rhodamine 6G (R6G) on this substrate optimized by controlling morphology and gold thickness showed that enhancement factor (2.30 × 10 7 ) and detection limit (10 −10 M) were both improved and represented better performance than its template AAO. Homogenous hot spots across the region of interest were achieved by scanning SERS intensity distribution for the band at 1505 cm −1 in 5 × 5 μm 2 area. Furthermore, the promising SERS activity of the flower-patterned substrate was theoretically explained through simulation of the electromagnetic field distribution. In addition, this SERS substrate is proposed for applications within the field of chemical and biochemical analyses.